Experimental Study on Seepage Characteristics of Fractured Rock Mass under Different Stress Conditions - Ma Haifeng; Yao Fanfan; Niu Xin’gang; Guo Jia; Li Yingming; Yin Zhiqiang; Li Chuanming (Geofluids)
In order to obtain the mechanical behavior and permeability characteristics of coal under the coupling action of stress and seepage, permeability tests under different confining pressures in the process of deformation and destruction of briquette coal were carried out using the electrohydraulic servo system of rock mechanics. The stress-strain and permeability evolution curves of briquette coal during the whole deformation process were obtained. The mechanical behavior and permeability coefficient evolution response characteristics of briquette coal under stress-seepage coupling are well reflected. Research shows that stress-axial strain curve and the stress-circumferential strain curve have the same change trend, the hoop strain and axial strain effect on the permeability variation law of basic consistent, and the permeability coefficient with the increase of confining pressure and decreases, and the higher the confining pressure, the lower the permeability coefficient, the confining pressure increases rate under the same conditions, and the permeability coefficient corresponding to high confining pressure is far less than that corresponding to low confining pressure. The confining pressure influences the permeability of the briquette by affecting its dilatancy behavior. With the increase of the confining pressure, the permeability of the sample decreases, and the permeability coefficient decreases with the increase of the confining pressure at the initial stage, showing a logarithmic function. After failure, briquette samples show a power function change rule, and the greater the confining pressure is, the more obvious the permeability coefficient decreases.